Answer:
![\frac{92}{15}](https://tex.z-dn.net/?f=%20%5Cfrac%7B92%7D%7B15%7D%20)
Step-by-step explanation:
change to improper
![\frac{24}{5} + \frac{4}{3}](https://tex.z-dn.net/?f=%20%5Cfrac%7B24%7D%7B5%7D%20%20%2B%20%20%5Cfrac%7B4%7D%7B3%7D%20)
this gives us
![\frac{92}{15}](https://tex.z-dn.net/?f=%20%5Cfrac%7B92%7D%7B15%7D%20)
final answer
plz mark as brainliest
Answer:
You are correct,y = 0.
Step-by-step explanation:
y = 4 x -3 + 12
y = -12 + 12
y = 0
Hope that helps!
The answer is: Substitution property of equality.
The explanation is shown below:
1. To solve this problem you must apply the proccedure shown below:
2. When you clear the variable x from the first equation, and subtitute it into the second equation, you obtain:
<span>3x−2y=10
x=(10+2y)/3
4x−3y=14
</span>4[(10+2y)/]−3y=14
<span> y=-2
3. When you subsitute y=-2 into the first equation and clear the x, you have:
x=2
</span>